A FINDING LIST OF HIGH LUMINOSITY STARS IV - MUNCH, LUIS (Observatorio Astrofísico de Tonantzintla, Pue, Pue, Mex, 1959)
A catalogue of 41 new OB stars classified between l=180° and 270°, and b=+6° and -6° is presented.
BOL OBS TONAN TACUB
Keywords: FINDING, LIST, HIGH, LUMINOSITY, STARS IV; ASTRONOMIA Y ASTROFISICA; COSMOLOGIA Y COSMOGONIA; ESTRELLAS